The association of the HLA‐A*24:02, B*39:01 and B*39:06 alleles with type 1 diabetes is restricted to specific HLA‐DR/DQ haplotypes in Finns. (10th February 2017) - Mikk, M.‐L.; Heikkinen, T.; El‐Amir, M. I.; Kiviniemi, M.; Laine, A.‐P.; Härkönen, T.; Veijola, R.; Toppari, J.; Knip, M.; Ilonen, J.; ,
Abstract : Background: We analysed the previously reported association of the HLA‐A*24:02, B*18 and B*39 alleles with type 1 diabetes and diabetes associated autoimmunity in the Finnish population applying HLA‐DR/DQ stratification. Materials & methods: Haplotype transmission was analysed in 2424 nuclear families from the Finnish Paediatric Diabetes Register. Survival analysis was applied to study the development of islet autoantibodies and further progression to clinical diabetes in the prospective follow‐up cohort from the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Study. The subjects were genotyped for specific HLA class I alleles by sequence‐specific hybridization using lanthanide labelled nucleotide probes. Results: The HLA‐B*39:06 allele was found almost exclusively on the (DR8)‐DQB1*04 haplotype in which its presence changed the disease risk status of the whole haplotype from neutral to predisposing. The HLA‐A*24:02 and the B*39:01 alleles increased the diabetes‐associated risk of the DRB1*04:04‐DQA1*03‐DQB1*03:02 haplotype but the alleles were in linkage disequilibrium and no independent effect could be detected. Within the DIPP cohort, neither the A*24:02 nor the B*39:01 allele were associated with seroconversion but were in contrast associated with increased progression from seroconversion to clinical disease. Discussion & Conclusions: The independent predisposing effect of the HLA‐B*39:06 allele with type 1 diabetes was confirmed in the Finnish population but the association of the A*24:02 and B*39:01 alleles remained inconclusive whilst both A*24:02 and B*39:01 affected the progression rate from seroconversion to autoantibody positivity to overt type 1 diabetes.